Penerapan Model Peer Teaching untuk Meningkatkan Hasil Belajar Sosiologi Peserta Didik SMA - Joi; Esi Mau Bodda (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2025)
This study aims to improve learning outcomes in Sociology by implementing the peer teaching model among tenth-grade students at SMA Muhammadiyah Kupang. The main problems identified were low student participation and learning outcomes that did not meet the minimum competency criteria. The peer teaching model was selected because it encourages collaborative interaction through the role of peer tutors who assist classmates in understanding learning materials. This research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data collection techniques included observation and achievement tests, which were analyzed qualitatively and quantitatively. The findings indicate an improvement in students' learning outcomes and learning engagement across the two cycles. In the first cycle, most students had not achieved satisfactory performance, while in the second cycle, 100% of students achieved learning mastery. These results demonstrate that the peer teaching model is effective in enhancing students’ understanding and performance in Sociology. Therefore, peer teaching can be recommended as an alternative participatory and student-centered learning strategy.